NILAI EKONOMI NIKEL INDONESIA AKIBAT PENERAPAN UNDANG –UNDANG NOMOR 4 TAHUN 2009 - Deddy Ahmad Fajar; Farah Nur Fauziah; Wibisono (El-Idaarah, 2021)
The government carries out a hedging policy on mineral and stone minesembers that have not been downstreamed through Law Number 04 of 2009 concerningMineral and Coal Mining. Implementation of the policies of Law No. 04 of the year2009 created a polemic for countries that needed nickel as raw materialthe main driver of their industry. Especially the European Union which is the third largest marketfor Indonesian nickel exports. China is also affected by the implementation of this law.This article will discuss the implications of Law No. 4 of 2009 concerningminerals and coal to the value of Indonesian nickel. Especially the author will discussimplications for the European Union and China. This research method uses qualitative methodsby studying literature from various sources and several fundamental theories forgain a more in-depth understanding of the problem under study.The conclusion is the strategic economic value of nickel, including developmentindustry today. Law No. 4 of 2009 issued by Indonesia is actually forincrease the value of nickel and take full control of Indonesia's natural wealth. Related to someCountries that need nickel as an industrial material should respect the law andIndonesian rules by taking an elegant approach